Differences of Fruit-Vegetable Consumption, Blood Pressure In Highland And Lowland - Afriyana Siregar; Arie Krisnasary; Demsa Simbolon (Poltekkes Kemenkes Jakarta III, 2021)
Consumption of vegetables and fruit daily can prevent degenerative diseases such as coronary heart disease, stroke, and cancer. One of the causes is unstable blood pressure. This study aimed to determine the differences in the consumption of vegetables, fruit, and blood pressure in highland (mountains) and lowland (coastal) communities in Bengkulu. This research was observational analytic with a cross-sectional approach. A sample of 65 people in the highlands (Kepahiang) and 65 people on the coast (Pasar Ikan) was purposive sampling. Statistical test using independent t-test. This study indicates that the average consumption of vegetables in the highlands is 170.33 grams/day, and fruit consumption is 100.96 grams/day. In comparison, the consumption of vegetables in the lowlands is 165.65 grams/day. Moreover, fruit consumption in the lowlands is 187.26 grams/day. In the highlands, the mean systolic blood pressure was 134.72 mmHg, and the diastolic was 83.18 mmHg, while the mean systolic blood pressure was 126.62 mmHg, and the diastolic 75.71 mmHg. This study concludes that there is no difference between vegetable consumption in the highlands and the lowlands, but there are differences in fruit consumptionand systolic diastolic blood pressure in the highlands and the lowlands. In health services, the existing Gerakan Masyarakat Hidup Sehat (GERMAS) program should be promoted.